More Scottish than British the 2011 Scottish Parliament Election - Carman, Christopher; Johns, Robert; Mitchell, James; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Using official statistics, this book explores how the SNP managed to confound expectations and win a parliamentary majority in the 2011 Scottish General Election. Perhaps surprisingly, it was not constitutional politics or the return of the Conservatives to power in Westminster but domestic issues that decided the vote in the SNP's favour.
Keywords: Political science; Comparative politics; Democracy; Public policy; Great Britain -- Politics and government; Europe -- Politics and government; Political Science and International Relations; British Politics; Comparative Politics; Political Science; Public Policy; European Politics; Democracy